2007
DOI: 10.1136/oem.2007.033654
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment for temporal confounders in a reanalysis of a case–control study of beryllium and lung cancer

Abstract: In this reanalysis, average, but not cumulative, beryllium exposure was related to lung cancer risk after adjustment for birth cohort. Confounding by birth cohort is likely related to differences in smoking patterns for workers born before 1900 and the tendency for workers hired during the World War II era to have been older at hire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
19
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 15 publications
1
19
1
Order By: Relevance
“…Beryllium has also been found to cause bone and lung cancer in several species of laboratory animals6 7 and has shown possible associations with nervous system cancer7 and kidney disease in humans 8 9. The International Agency for Research on Cancer has designated beryllium a group 1 human carcinogen,7 10 based on toxicological studies and findings of increased lung cancer risk among individuals enrolled in a beryllium case registry11 or employed in the US beryllium processing industry 9 12…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Beryllium has also been found to cause bone and lung cancer in several species of laboratory animals6 7 and has shown possible associations with nervous system cancer7 and kidney disease in humans 8 9. The International Agency for Research on Cancer has designated beryllium a group 1 human carcinogen,7 10 based on toxicological studies and findings of increased lung cancer risk among individuals enrolled in a beryllium case registry11 or employed in the US beryllium processing industry 9 12…”
mentioning
confidence: 99%
“…Since the publication of this study, beryllium exposure estimates have been developed through the creation of job–exposure matrices (JEMs) at three plants in the study. A lung cancer nested case–control study at one of these plants found elevations associated with average and maximum exposure 12 13. With quantitative exposure estimates available at two additional plants, we extended follow-up of the cohort of workers in all seven facilities, focussing on the three plants with quantitative exposure estimates.…”
mentioning
confidence: 99%
“…Although this confounding was not considered in the original analysis, most positive associations between lagged beryllium exposure and lung cancer remained after adjusting for birth cohort. 12 Critics of the study design have claimed that the results were biased, in part, due to the use of risk-set sampling in conjunction with exposure lagging. 13,14 Two simulation studies to evaluate the nested case-control study design in conjunction with exposure lagging did not observe bias.…”
mentioning
confidence: 99%
“…Schubauer-Berigan and colleagues3 conducted a reanalysis of a nested case–control study of beryllium and lung cancer originally published by Sanderson and colleagues 4. The reanalysis makes a valuable contribution by strengthening the original study’s finding of an association between beryllium and lung cancer.…”
mentioning
confidence: 99%
“…Deubner and colleagues (with financial support from a major beryllium producer) have criticised the Sanderson study, prompting Schubauer-Berigan's reanalysis published in the current issue 3. Deubner’s letter,10 Sanderson’s response11 and now the Schubauer-Berigan reanalysis illustrate the constructive contributions of open debate in science.…”
mentioning
confidence: 99%